2008
DOI: 10.4102/sajp.v64i1.98
|View full text |Cite
|
Sign up to set email alerts
|

Plasma levels of beta-endorphin and serotonin in response to specific spinal based exercises

Abstract: The results of this study showed that spinal stabilisation and treadmill walking exercises produced significant increase in plasma serotonin levels (P < 0.05) however there were no significant changes in the plasma levels of beta-endorphin in all the exercise groups (P > 0.05).It could be that biochemical effects associated with stabilisation and treadmill walking exercises therefore may involve production of serotonin and its release into the plasma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…A model of stabilization exercise programme presented in this study began with audio visual information related to the spine and how the spine and local stability muscles work together to protect the spine was provided to aid mental imagery of correct performance prior to carrying out proper stabilization exercise protocol. Stabilization exercise protocols used in this study were similar to the one used in the previously reported studies 2,3,5 Control Group Participants allocated to the control group received no exercise treatment during the time the study was carried out.…”
Section: Interventionsmentioning
confidence: 99%
See 4 more Smart Citations
“…A model of stabilization exercise programme presented in this study began with audio visual information related to the spine and how the spine and local stability muscles work together to protect the spine was provided to aid mental imagery of correct performance prior to carrying out proper stabilization exercise protocol. Stabilization exercise protocols used in this study were similar to the one used in the previously reported studies 2,3,5 Control Group Participants allocated to the control group received no exercise treatment during the time the study was carried out.…”
Section: Interventionsmentioning
confidence: 99%
“…A recent focus in the physiotherapy management of chronic low back pain has been to identify specific muscles that are best able to stabilize the back and to carry out spinal stabilization exercises to enhance those muscles whose primary function is considered dynamic stabilization and segmental control of the spine 2 . Currently there is evidence demonstrating the efficacy of stabilization exercises on pain, functional disability and quality of life in sufferers with acute and chronic low back disorders 2 .The effects of stabilization exercise approach may be multifactorial involving physiological, psychological and other mechanisms yet to be well investigated 3 . The likelihood of muscular contraction during spinal stabilization exercises providing sensory input to activate different pain inhibitory mechanisms appeared to have been suggested to little investigation.…”
Section: A Randomized Controlled Trial (Rct) On the Effects Of Frequementioning
confidence: 99%
See 3 more Smart Citations